Kontribusi Pondok Pesantren dalam Meningkatkan Pemberdayaan Ekonomi Umat - Farah Qalbia; M. Reza Saputra (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to analyze the contribution of Islamic boarding schools (pesantren) in enhancing the economic empowerment of the community. The method used is a literature review with a qualitative approach. The results show that Islamic boarding schools have great potential in community economic empowerment through three main strategies: 1) Empowering the quality of students through entrepreneurship training, 2) Financial and capital empowerment by acting as Baitul Maaal wa Tamwil, and 3) Product development by involving students in MSME innovation. The implementation of these strategies can make Pesantren a centre for economic empowerment that contributes to improving the welfare of the surrounding community. This study concludes that optimizing the function of pesantren not only as educational institutions but also as agents of community economic empowerment has the potential to have a significant impact on community economic development.